PENINGKATAN SKILL MAHASISWA KEBIDANAN MELALUI PELATIHAN BABY MASAGE SEBAGAI ALTERNATIF USAHA MANDIRI - Else Sri Rahayu Else; Kosma Heryati; Rialike Burhan; Elvi Destariyani (LPPM Universitas Al Muslim, 2022)
Infancy is a golden period for baby growth and development so it needs special attention. Physical growth is influenced by internal and external factors. One of them is the technique of giving baby massage therapy. Monitoring and stimulating the growth and development of the baby is one of the duties of the midwife. This community service activity aims to increase insight, especially about complementary based holistic midwifery services, complementary based enterpreneurial skill and independence. The implementation of this community service activity is carried out through the following stage: 1) conducting webinars through zoom meetings in the form of education for final year students, namely exposure to basic knowledge of baby massage; 2) collaboration of midwifery students with a team of lecturers, baby massage business owners, and trainers in the implementation of baby massage; 3) individual stimulation for practice implementation of baby massage under the guidance of a team of lecturers; and 4) implementation of baby massage and direct education to mothers by trained final year students. Based on this communit service activity, it can be concluded that by increasing skills and understanding the importance of entrepreneurial spirit about baby massage as an additional insight for final year professional students.